2021
DOI: 10.1097/ceh.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

A Seat at the Table: Delivering Effective Infectious Diseases and Antimicrobial Stewardship Education to Advanced Practice Providers at an Academic Medical Center

Abstract: Introduction:Antimicrobial Stewardship programs promote appropriate antimicrobial use through different avenues, including education. Advanced Practice Providers (APPs) provide inpatient care in a wide-range of settings. Little is known about the educational needs of APPs at academic medical centers or the effect of educational interventions directed at inpatient APPs on clinical care. Our study looked at the effect of an educational intervention on antimicrobial prescribing by APPs for asymptomatic bacteriuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 29 , 30 It is not surprising that early studies found APPs did not have favorable perceptions of ASP interactions. One early study of NPs at a tertiary care medical center found a majority (66%) reported they were “not familiar” with the center’s ASP and only 17% reported finding ASP interactions “useful” or “very useful.” 27 More recent studies suggest that ASP engagement of APPs is increasing with several more recent studies of APPs finding that the majority of NPs and/or PAs now report ASPs as helpful sources for ID and antimicrobial education were “somewhat useful or useful.” 24 , 25 …”
Section: How Have Asps Historically Engaged With Apps?mentioning
confidence: 99%
See 3 more Smart Citations
“… 29 , 30 It is not surprising that early studies found APPs did not have favorable perceptions of ASP interactions. One early study of NPs at a tertiary care medical center found a majority (66%) reported they were “not familiar” with the center’s ASP and only 17% reported finding ASP interactions “useful” or “very useful.” 27 More recent studies suggest that ASP engagement of APPs is increasing with several more recent studies of APPs finding that the majority of NPs and/or PAs now report ASPs as helpful sources for ID and antimicrobial education were “somewhat useful or useful.” 24 , 25 …”
Section: How Have Asps Historically Engaged With Apps?mentioning
confidence: 99%
“…24 In addition, APPs practicing at one academic medical center reported "Attending or Fellow Decision" as the most common barrier to decreasing inappropriate antimicrobial prescriptions. 25 Another study found that "fear of offending senior clinician" is a commonly cited factor in antibiotic decision-making among NPs. 26 How have ASPs historically engaged with APPs?…”
Section: What We Know About App Antimicrobial Usagementioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, there are limited published data on methodologies and outcomes related to their involvement. [8][9][10][11][12][13] Previously published studies have limited their scope to specific practice settings and have small sample sizes. 14 Given diverse learning backgrounds and differential emphasis on antimicrobial stewardship education in their training, compared to MDs and DOs, it is important to approach education implementation with a collaborative and tailored approach.…”
Section: Introductionmentioning
confidence: 99%